Blast Protection of Infrastructure with Fluid Filled Cellular Polymer Foam. (2017) - Venkataramana, K.; Singh, Ram Kumar; Deb, Anindya; Bhasin, Vivek; Vaze, K.K.; Kushwaha, H.S.
Abstract: Full field blast experiments were performed to assess the potential of fluid filled polymer foam for blast mitigation. The experiments involve air blast loading of clamped mild steel plates covered with fluid filed polymer foam for blast protection. The deformation profiles and maximum deflections of plates are compared with and without foam protection. The experimental results indicate a reduction in the plate deflection up to 50% with foam protection.